Phase I Pharmacokinetic and Pharmacodynamic Study of 17-dimethylaminoethylamino-17-demethoxygeldanamycin, an Inhibitor of Heat-Shock Protein 90, in Patients With Advanced Solid Tumors - Ramanathan, Ramesh K. (American Society of Clinical Oncology, 2010)
PURPOSE: To define the maximum tolerated dose, toxicities, pharmacokinetics, and pharmacodynamics of 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17DMAG). METHODS: 17DMAG was given intravenously over 1 hour daily for 5 days (schedule A) or daily for 3 days (schedule B) every 3 weeks. Plasma 17DMAG concentrations were measured by liquid chromatography/mass spectrometry. Heat-shock proteins (HSPs) and client proteins were evaluated at baseline and after treatment on day 1 in peripheral blood mononuclear cells (PBMCs) and in pre- and post-treatment (24 hours) biopsies done during cycle 1 at the recommended phase II dose (n = 7). RESULTS: Fifty-six patients were entered: 26 on schedule A; 30 on schedule B. The recommended phase II doses for schedules A and B were 16 mg/m(2) and 25 mg/m(2), respectively. Grade 3/4 toxicities included liver function test elevation (14%), pneumonitis (9%), diarrhea (4%), nausea (4%), fatigue (4%) and thrombocytopenia (4%). There were no objective responses. Four patients had stable disease. 17DMAG half-life was 24 ± 15 hours. 17DMAG area under the curve (range, 0.7 to 14.7 mg/mL × h) increased linearly with dose. The median HSP90, HSP70, and integrin-linked kinase levels were 87.5% (n = 14), 124% (n = 20), and 99.5% (n = 20) of baseline. Changes in HSPs and client proteins in tumor biopsies were not consistent between baseline and 24 hours nor did they change in the same direction as those in PBMCs collected at the time of biopsy. CONCLUSION: The recommended phase II doses of 17DMAG (16 mg/m(2) × 5 days or 25 mg/m(2) × 3 days, every 3 weeks) are well tolerated and suitable for further evaluation.